Qur’anic Foundations of the Obligation to Learn: A Thematic and Scientific Exegesis and Its Implications for Islamic Education - Muzami, Fazrin Syaibatul Hamdi; Nuraida, Siti Vania; Saidah, Saidah; Rostika, Ika (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2025)
This study departs from the growing urgency of strengthening Islamic education in nurturing knowledgeable and ethical individuals, as emphasized repeatedly in the Qur’an and Hadith. While previous studies often treat the obligation to learn in a normative and descriptive manner, they rarely integrate thematic exegesis (tafsir maudhū‘ī) and scientific exegesis (tafsir ‘ilmi) as combined analytical frameworks. This research fills that gap by examining Qur’anic educational verses through both epistemological approaches. Using a library research method, the study analyzes relevant Qur’anic passages alongside classical and contemporary scholarly works. The findings reveal that thematic exegesis systematically organizes Qur’anic guidance on learning into a coherent conceptual framework, whereas scientific exegesis contextualizes these teachings through the dialogue between revelation and modern scientific insights. When employed together, the two approaches generate a comprehensive educational paradigm that emphasizes literacy, intellectual cultivation, and social responsibility. The study carries direct implications for contemporary Islamic education, particularly in designing integrative curricula, strengthening literacy culture, and reframing the obligation to learn as both an act of worship and a civilizational mandate. Ultimately, the research reaffirms the pivotal role of Islamic education in shaping a knowledgeable, just, and morally grounded society. Penelitian ini berangkat dari urgensi penguatan pendidikan Islam dalam membentuk manusia berilmu dan berakhlak, sebagaimana ditegaskan dalam Al-Qur’an dan hadis. Kajian terdahulu umumnya membahas kewajiban belajar secara normatif dan deskriptif, namun belum mengintegrasikan tafsir maudhu’i dan tafsir ilmi sebagai kerangka analitis yang saling melengkapi. Penelitian ini mengisi celah tersebut dengan mengkaji ayat-ayat pendidikan melalui kedua pendekatan epistemologis tersebut. Menggunakan metode studi pustaka, penelitian menelaah ayat-ayat Al-Qur’an terkait perintah belajar, didukung literatur klasik dan kontemporer. Hasil penelitian menunjukkan bahwa tafsir maudhu’i menyusun bimbingan Qur’ani tentang kewajiban belajar ke dalam kerangka konsep yang sistematis, sedangkan tafsir ilmi mengontekstualisasikannya melalui dialog antara wahyu dan temuan ilmiah modern. Penggabungan keduanya melahirkan paradigma pendidikan Islam yang menekankan literasi, pengembangan akal, dan tanggung jawab sosial. Penelitian ini berdampak langsung pada pengembangan pendidikan Islam kontemporer, khususnya dalam perancangan kurikulum integratif, penguatan budaya literasi, serta pemaknaan ulang kewajiban belajar sebagai ibadah sekaligus misi peradaban. Dengan demikian, penelitian ini menegaskan kembali peran sentral pendidikan Islam dalam membangun masyarakat yang berilmu, berkeadilan, dan berkarakter.